560 Mechanical Thrombectomy Versus Best Medical Therapy for Medium Vessel Occlusions: A Cost-Effective Analysis Using Local Get with the Guidelines Registry Data. (April 2023) - Lim, Jaims; Monteiro, Andre; Siddiqi, Manhal; Kuo, Cathleen; Baig, Ammad; Khawar, Wasiq; Davies, Jason; Levy, Elad I.; Siddiqui, Adnan Hussain
Abstract : INTRODUCTION: Equipoise exists in regards to whether mechanical thrombectomy (MT) is superior to best medical management (BMM) in patients with acute ischemic stroke due to medium vessel occlusion (MeVO). While clinical outcome differences may not be statistically significant in prior series, MT for MeVO may still be cost-effective (CE). METHODS: The local Get with the Guidelines (GTWG) registry data was queued. Patients with MeVO documented on CTA presenting with NIHSS >5 and treated with MT or BMM within 12 hours from symptom onset were included. Rates of each mRS outcomes was collected. Stroke cost data was derived from previous stroke literature including costs associated with imaging done at admission (non-contrast CT, CT Angiography, and CT perfusion), MRI 24 hours post-stroke, perfusion maps software, intravenous alteplase, physician and personnel costs, and thrombectomy. Costs associated with each mRS from presentation to 90-days and post-90 day care were collected. Utilizing the clinical data from GTWG registry and costs from the literature, TreeAge Pro was used to generate cost-effectiveness ratios (CE-ratio). RESULTS: Both the MT and BMM groups were similar in age, comorbidities, NIHSS and time to presentation. MT was found to be more cost-effective (CE-ratio 93, 500) compared to BMM (CE-ratio 101, 496. MT was more costly (total cumulative cost 59, 840) than BMM (total cumulative cost 51, 763). MT and BMM respectively had an effectiveness score of 0.64 and 0.51. CONCLUSIONS: This is one of the first CE studies comparing MT and BMM in acute ischemic strokes due to MeVO. We demonstrate based on GTWG data and costs in the literature that MT is more CE than BMM.